Analysis of curative effect of Vancomycin combined with Meropenem as empirical treatment of peritoneal dialysis-related peritonitis - WANG Chan-yuan; WU Yong-gui; QI Xiang-ming; WANG Juan; ZHAO Min; DAI Hong; LU Wen (Linchuang shenzangbing zazhi)
Objective To analyze the curative effect of Vancomycin combined with Meropenem as empirical treatment of peritoneal dialysis-related peritonitis,and provide the basis for clinical empiric therapy.Methods A total of 106 cases of PD-related peritonitis from the First Affiliated Hospital of Anhui Medical University between June 2011 and June 2014 were reviewed,and divided into two groups according to the initial empirical treatments:Vancomycin combined Meropenem as the treatment group,and Vancomycin combined others(the third-generation cephalosporins or aminoglycosides) as the control group.The white blood cells were counted and drug sensitivity test was done.Clinical data,pathogens,resistance and outcomes of the 106 cases of peritoneal dialysis-related peritonitis were analyzed retrospectively.Results Most of pathogens were gram-positive aureus.Drug sensitivity test of the gram-positive strains showed that the three antibiotics with lowest antibiotic resistance were Linezolid,Vancomycin and Moxifloxacin.Drug sensitivity test of the gram-negative bacteria showed that antibiotics with the lowest resistance were Meropenem,Tobramycin and Piperacillin tazobactam.The number of white blood cells in the peritoneal dialysate was significantly decreased in the patients treated with Vancomycin and Meropenem(P<0.05),and exit rate,mortality and mold detection rate were lower.Conclusions Vancomycin and Meropenem can rapidly reduce the number of white blood cells in the peritoneal dialysate,and are recommended as the initial empirical treatment in a part of peritoneal dialysis-related peritonitis.